Text-fig. 14. a, b: Acer aff. campestre. a: Oriolo MSF 664. b: Oriolo MSF 666. c, d: Acer aff. monspessulanum. c: Oriolo MSF 641. d: Oriolo MSF 662. e: Acer aff. opulus subsp. obtusatum Oriolo MSF 669. f, g: Acer aff. cappadocicum subsp. lobelii. f: Oriolo MSF 675. g: Oriolo MSF 631. h, i: Cornus sp. Oriolo MSF 655, two views of a strongly folded leaf impression. Scale bars 50 mm (a, e–g), 10 mm (b–d, h, i). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 14. a, b: Acer aff. campestre. a: Oriolo MSF 664. b: Oriolo MSF 666. c, d: Acer aff. monspessulanum. c: Oriolo MSF 641. d: Oriolo MSF 662. e: Acer aff. opulus subsp. obtusatum Oriolo MSF 669. f, g: Acer aff. cappadocicum subsp. lobelii. f: Oriolo MSF 675. g: Oriolo MSF 631. h, i: Cornus sp. Oriolo MSF 655, two views of a strongly folded leaf impression. Scale bars 50 mm (a, e–g), 10 mm (b–d, h, i). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 243, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867